Determinan keputusan Generasi Z dalam investasi Reksa Dana Syariah dengan trust sebagai variabel mediator - Uun Sunarsih; Zainal Umaaya (LPMP Imperium, 2025)
This study aims to examine the influence of minimum capital, religiosity, and Islamic financial literacy on the demand for Islamic mutual fund investment with trust as a mediating variable among Generation Z in Indonesia. This study uses a quantitative research type with an associative approach. The population of this study is Generation Z in Indonesia, and the sample was obtained using the Isaac and Michael formula, yielding 405 respondents. The data are primary, and the analysis is performed using CB-SEM. This study shows that minimum capital requirements impact trust, with higher requirements leading to greater public confidence in Islamic investment. Religiosity enhances trust; the more religious a person is, the more they adhere to Islamic principles. Additionally, better Islamic financial literacy increases trust in fundraisers. Trust also influences interest in Islamic mutual fund investments, suggesting emotional factors play a role. Minimum capital and religiosity both affect investment interest, with trust acting as a mediator. Islamic financial literacy significantly shapes investment intentions, again mediated by trust. Public interest statements The findings highlight the importance of trust in boosting investment interest in Islamic mutual funds among Generation Z. Therefore, strategies for literacy education, product transparency, and affordable initial capital are essential.